The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2109.2007.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish farming on nutrients and benthic community structure in the Eastern Aegean (Turkey)

Abstract: The impact of a sea bass (Dicentrarchus labrax L., 1758) farm on water quality and benthic community structure was investigated at a fish farm site in Engeceli Bay (western part of Izmir Bay) between April 2001 and February 2002. The characteristics of the water column in the fish farm were investigated in terms of physical and chemical parameters. Concentrations of nitrate, phosphate and ammonium ions in all sampling stations within the Bay were compared with the water quality parameters measured at the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 24 publications
5
43
3
2
Order By: Relevance
“…For cage aquaculture studies in developed coastal regions, it may be extremely difficult to find reference sites, remote enough from other aquaculture operations or other anthropogenic sources, while still reflective of farmexposed hydrodynamics (Troell et al 2003). Where baseline data are unavailable, sampling of multiple reference sites can be a powerful assessment tool to help ensure ambient spatial variability is captured (Fernandes et al 2001, Merceron et al 2002, Yucel-Gier et al 2007, Rodríguez-Gallego et al 2008. However, many studies have only a single reference location, presumably due to practical constraints.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…For cage aquaculture studies in developed coastal regions, it may be extremely difficult to find reference sites, remote enough from other aquaculture operations or other anthropogenic sources, while still reflective of farmexposed hydrodynamics (Troell et al 2003). Where baseline data are unavailable, sampling of multiple reference sites can be a powerful assessment tool to help ensure ambient spatial variability is captured (Fernandes et al 2001, Merceron et al 2002, Yucel-Gier et al 2007, Rodríguez-Gallego et al 2008. However, many studies have only a single reference location, presumably due to practical constraints.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…Karakassis et al 1998;Yucel-Gier et al 2007;Borja et al 2009) have shown that the environmental effects of fish farm activities are limited to areas immediately beneath the cages.…”
Section: Sampling and Sampling Pointsmentioning
confidence: 99%
“…Some studies have analysed metals and pigments found in sediments as well as bacteria and multiple stable isotopes as indicators of environmental impact (Mazzola et al 2000;Kaymakci et al 2010). Others have focused on the environmental impact of aquaculture activities on nutrients and plankton (Neofitou and Klaoudatos 2008); on nutrients and benthic community structure (Mazzola et al 2000;Yucel-Gier et al 2007); and on the geochemistry of sediments and benthic organisms Mazzola et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The effluents of cage culture, mainly uneaten food, and faecal and urinary products, are released directly into the environment and result in many environmental problems such as eutrophication, fish growth retardation, and changes of benthos communities (Silvert 1992;Beveridge 1996;Liu et al 1997;Guo and Li 2003;Yucel-Gier et al 2007). Traditionally environmental monitoring has concentrated on a few key physical and chemical variables and organisms, but in recent years, increasing numbers of studies have focused on wholesystem environmental assessment, including considerations of the assimilative capacity of specific systems and their ability to absorb and dilute perturbations (Osparcom 1998;Maroni 2000;Fernandes et al 2001).…”
Section: Introductionmentioning
confidence: 99%